Trilingual Mobile Dictionary for Malaysian School Students - Wong, Szee Yung (2021)
In Malaysia, most of the school students are required to study three languages which are Malay, Chinese and English. To some extent, the relationship among the three languages may help those school students to understand the words they have come up with or obtained. As we know, dictionary is one of the essential mediums for learning any language. Along with the rapid growth of mobile technologies at this era, numerous mobile applications were extensively developed as a media for learning. In fact, dictionaries on handheld devices such as smartphones and tablets are more realistic and convenient than the conventional dictionaries as it would not restrict by the time and space limitation, where this allows users to easily retrieve the information at anytime and anywhere. Moreover, the procedures of flipping and searching a particular vocabulary among three languages from the conventional dictionaries is challenging, time consuming and not effective at all. Thus, the aim of this project is to assist Malaysia school students in their learning by simplifying the process of accessing the dictionaries data. At the same time, the interactive tools that are available in the mobile application might be able to boost up the performance of Malaysian school students in learning vocabularies. In order to evaluate the common features that are important for Malaysian school students and to figure out any valuable core functions that are not supported by any other existing applications, a literature review on the latest comparable mobile applications was undertaken. On the other hand, evolutionary prototyping development methodology is adopted to continually cater with the version upgrades and user feedback. Furthermore, user acceptance testing was carried out with five invited participants, where these participants are the mixture of primary school students and secondary school students. As a result, most of the students are able to search and understand the information shown in the mobile dictionary application without spending much time. In short, the project has successfully met the main goal which is allowing Malaysian school students to translate and learn the vocabularies in an effective and convenient way.